Histopathological Changes in Endometrial Biopsies of Patients with Abnormal Uterine Bleeding - Ali, Iman I; Al-Shikey Ainour; Abouzrig Ghazala; Omar O. Ghazala; Arhoma Amal; AL-Gheryani, Nabeia (International Journal of Medical Research and Review, 2023)
Introduction: Abnormal uterine bleeding (AUB) is one of the commonest complaints leading to endometrial sampling by endometrial biopsy or curettage. Histopathological analysis revealed various patterns ranging from normal endometrium to malignancy and histopathological examination helps in the diagnosis of these diseases presenting with abnormal uterine bleeding. Objective: To assess the causes of AUB in reproductive, perimenopausal and menopausal women. Methodology: This is a retrospective study that includes a total of 375patients’specimens of endometrial biopsies which were clinically diagnosed as AUB in the department of pathology, faculty of medicine, the university of Benghazi from January 2009 to March 2010. The age of the patient ranged from 20 -80 years, and the mean age was (47.38yr). The patient was categorized into 3 groups with 198 cases in the perimenopausal age group,103 cases in the postmenopausal age group and only 74 cases in the reproductive age group. Results: in this study, the prevalence of non-neoplastic endometrial change was commonly seen in the perimenopausal and reproductive age groups (58.2%), (26.8%) respectively, whereas few cases in the postmenopausal age group (15%). The neoplastic endometrial changes (benign, premalignant, malignant) were commonly seen among the perimenopausal age group, followed by the postmenopausal age group, while neoplasia was rare in the reproductive age group. Conclusion: The causes of AUB depend on the age of the patient. In the reproductive age group, AUB was due to hormonal imbalance, while in perimenopausal and postmenopausal women it was generally due to hyperplasia and malignancy.